The impact of electoral systems on women’s participation in decision- making level (Mongolian Journal of Humanities and Social Sciences, 2024)
Ensuring gender equality in legislative bodies plays a significant role in establishing democracy, human rights, and equality. The Government of Mongolia has yet to fulfill its commitments and obligations to international organizations, prompting an exploration of opportunities to increase women's participation at the decision-making level. This article examines the state of women's participation in Mongolia's legislative body in connection with changes in the electoral system. The analysis is based on the theory of political electoral systems and empirical research findings on the relationship between electoral systems and women's representation and participation at the decision-making level across countries. It traces the historical developments from 1992 to the present, drawing conclusions about the 2024 election results and highlighting the decisive role of the electoral system in shaping women's participation.  This article aims to present the results of implementing and testing a “Mini” lesson method in the “Human and Society” social science methodology course at the Teachers’ School, focusing on student characteristics, interests, and individual differences. The study involved a total of 53 fourth-year students from two groups in the primary education program. Emphasizing the importance of addressing each student’s individual differences, the study highlights the use of Howard Gardner's multiple intelligences test as essential for identifying learner differences.The findings reveal that effectively organizing “Mini” lessons with role-playing, careful planning, structured teaching, and engaging discussions is key to successful implementation. Within the framework of this goal, it is noted that, in order to enhance the quality and effectiveness of education today, it is important to implement lessons and activities that consider each learner's differences. This aligns with global trends and the theories and concepts proposed by researchers and scholars, suggesting possibilities for incorporating these approaches into educational activities.Шийдвэр гаргах түвшний эмэгтэйчүүдийн оролцоон дахь сонгуулийн тогтолцооны нөлөөХураангуй: Хууль тогтоох байгууллагад жендэрийн тэгш байдлыг хангах нь ардчилал, хүний эрх, тэгш байдлыг тогтооход чухал нөлөөтэй. Монгол улсын Засгийн газар дэлхийн хамтын ажиллагааны байгууллагуудын өмнө хүлээсэн үүрэг, амлалтаа хараахан биелүүлээгүй байгаа нь шийдвэр гаргах түвшин дэх эмэгтэйчүүдийн оролцоог нэмэгдүүлэх боломжийг судлахад хүргэдэг. Энэ өгүүллээрээ улс төрийн сонгуулийн тогтолцооны онол болон дэлхийн улс орнуудын сонгуулийн тогтолцоо болоод эмэгтэйчүүдийн шийдвэр гаргах түвшин дэх оролцоо, төлөөлөл хоорондын хамаарлыг судалсан эмпирик судалгааны үр дүнд тулгуурлан Монголын хууль тогтоох байгууллага дахь эмэгтэйчүүдийн оролцооны төлөв байдлыг сонгуулийн тогтолцооны өөрчлөлттэй холбон 1992 оноос өнөөг хүртэл түүхчлэн авч үзлээ. 2024 оны сонгуулийн үр дүнд дүгнэлт хийж, эмэгтэйчүүдийн оролцоонд сонгуулийн тогтолцоо шийдвэрлэх үүрэгтэй болохыг тодорхойлов.Түлхүүр үг: Эмэгтэйчүүдийн оролцоо, квот, сонгуулийн тогтолцоо, улс төрийн нам, жендэрийн эрх тэгш байдал, тогтвортой хөгжлийн зорилт